Consequences of early postnatal benzodiazepines exposure in rats. I. Cognitive-like behavior - Mikulecka, Anna; Subrt, Martin; Stuchlik, Ales; Kubova, Hana (Frontiers in Behavioral Neuroscience, 2014)
Clinical and experimental studies suggest possible risks associated with the repeated administration of BZDS during the prenatal or early postnatal period on further development and behavior. In the present study, we assess short- and long-term effects of early exposure to clonazepam (CZP) on cognitive tasks. CZP (0.5 or 1.0 mg/kg/day) was administered from postnatal day (P)7 until P11, and animals were exposed to the following behavioral tests at different developmental stages: (1) a homing response test, which exploits the motivation of a rat pup to reach its home nest, was administered on P12, P15, P18 and P23 rats; (2) passive avoidance was tested in three trials (at 0 h, 2 h and 24 h intervals) on P12, P15, P18, P25 and P32 rats; (3) within- and between-session habituation was tested in an open field (OF) at P70; and (4) a long-term memory version of the Morris water maze (MWM) was tested at P80. A 1.0 mg/kg dose of CZP extended latency in the homing response and decreased the number of correct responses when tested at P12 and P23. In the first trial of the passive avoidance test, latency to enter a dark compartment was shorter in the CZP-exposed rats. Both treated and control animals older than P15 learned the passive-avoidance response at the same rate. Irrespective of the treatments, all adult animals showed within-session habituation. Between-session habituation, however, was found only in the controls. With respect to the MWM test, all animals learned to reach the platform, but animals exposed to higher doses of CZP spent more time swimming in the first acquisition test. No difference between groups was found in a repeated acquisition test (10 and 40 days after the first acquisition test). The results of the present study show that even short-term exposure to CZP alters behavioral responsiveness in pre-weaning, juvenile and adult animals. Not only were changes observed on conventional cognitive tests in our study, but the changes also seem to be related to